Highly air- and moisture-stable hole-doped carbon nanotube films achieved using boron-based oxidant. (2nd February 2017) - Funahashi, Kazuma; Tanaka, Naoki; Shoji, Yoshiaki; Imazu, Naoki; Nakayama, Ko; Kanahashi, Kaito; Shirae, Hiroyuki; Noda, Suguru; Ohta, Hiromichi; Fukushima, Takanori; Takenobu, Taishi
Abstract: Hole doping into carbon nanotubes can be achieved. However, the doped nanotubes usually suffer from the lack of air and moisture stability, thus, they eventually lose their improved electrical properties. Here, we report that a salt of the two-coordinate boron cation Mes2 B + (Mes: 2, 4, 6-trimethylphenyl group) can serve as an efficient hole-doping reagent to produce nanotubes with markedly high stability in the presence of air and moisture. Upon doping, the resistances of the nanotubes decreased, and these states were maintained for one month in air. The hole-doped nanotube films showed a minimal increase in resistance even upon humidification with a relative humidity of 90%.